LECTURERS' ATTITUDES TOWARDS ENGLISH VARIETY EXPOSURE IN INDONESIA - Alfan Hariri; Ahmad Munir; Syafiul Anam (Jurnal Education and Development, 2019)
This study was spawned from the lack of research of English varieties concept in Indonesia. In this study the lecturers’ attitude toward the English varieties is explored as well as their view about using the English varieties in the classroom. The study uses qualitative research design to seek the participant attitude toward the English varieties. The subjects of the study of this research are ten lecturers of three higher educations in Surabaya; two privates and one state university with ten lecturers in total. To collect the data, the prompt-production will be used to explore in depth lecturers’ attitude. One of the more significant findings to emerge from this study is that the differences between the international graduated lectures and national graduated lectures in term of their attitude toward the English varieties. Furthermore, this attitude also influences their perception about teaching the varieties in English language teaching (ELT) classroom.